1995
DOI: 10.1021/np50121a006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Evaluation of New Plant-Derived Compounds That Inhibit HIV-1 Reverse Transcriptase

Abstract: Swertifrancheside [1], a new flavonone-xanthone glucoside isolated from Swertia franchetiana, 1 beta-hydroxyaleuritolic acid 3-p-hydroxybenzoate [2], a triterpene isolated from the roots of Maprounea africana, and protolichesterinic acid [3], an aliphatic alpha-methylene-gamma-lactone isolated from the lichen Cetraria islandica, were found to be potent inhibitors of the DNA polymerase activity of human immunodeficiency virus-1 reverse transcriptase (HIV-1 RT), with 50% inhibitory doses (IC50 values) of 43, 3.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…S. hookeri extract is used in the treatment of microbial infections and as a mood elevator [97]. Swertifrancheside isolated from S. franchetiana was found to be potent inhibitor of the DNA polymerase activity of human immunodeficiency virus-1 reverse transcriptase [98]. Naturally occurring xanthones have emerged as an important class of organic compounds in view of their remarkable pharmacological and other biological activities.…”
Section: Biological Activities Of Xanthonesmentioning
confidence: 99%
“…S. hookeri extract is used in the treatment of microbial infections and as a mood elevator [97]. Swertifrancheside isolated from S. franchetiana was found to be potent inhibitor of the DNA polymerase activity of human immunodeficiency virus-1 reverse transcriptase [98]. Naturally occurring xanthones have emerged as an important class of organic compounds in view of their remarkable pharmacological and other biological activities.…”
Section: Biological Activities Of Xanthonesmentioning
confidence: 99%
“…Finally, swertifrancheside was found to be a potent inhibitor of the DNA polymerase activity of HIV-1 reverse transcriptase (Pengsuparp et al, 1995), and five tetrahydroxyxanthones isolated from Tripterospermum lanceolatum were shown to have a strong inhibitory effect on the activity of Moloney murine leukemia virus reverse transcriptase (Chang et al, 1992). The tetrahydroxyxanthones also inhibited angiotensin-1-converting-enzyme (ACE) activity in a dose-dependent manner (Chen et al, 1992).…”
Section: Saccifolieaementioning
confidence: 99%
“…These secondary metabolites from other plants have shown bioactivity, as it is indicated elsewhere were flavonoids (Pengsuparp et al, 1995) and alkaloids (McMahon et al, 1995) contain anti-HSV activity. According to the study done by Sassi et al (2008), C. trifurcatum grown elsewhere exhibited in vitro anti-HSV activity, also, Stanberry et al (1986) indicated, Pyrerhrins the active insecticide from C. cinerariaefolim exhibited in vitro anti HSV activity.…”
Section: Discusionmentioning
confidence: 73%